Cognitive training for people with dementia: A Cochrane review: Dementia care research: Behavioral interventions. (7th December 2020) - Bahar‐Fuchs, Alex; Martyr, Anthony; Goh, Anita M Y; Sabates, Julieta M; Clare, Linda
Abstract: Background: Cognitive training (CT) has been found by previous reviews to be ineffective in relation to cognitive and non‐cognitive outcomes among people with neurodegenerative or vascular dementias (Bahar‐Fuchs et al. 2013). However, the quality of trials has been regarded as low, and numerous new trials have been completed in recent years. Here we present findings of a comprehensive update to this review (Bahar‐Fuchs et al. 2019). Methods: 33 RCTs were eligible for inclusion, 11 of which were included in our 2013 review. Study characteristics and data required for effect size calculations were extracted and Risk of Bias for each study was rated in duplicate. Change from baseline was used to calculate effect estimates (Hedges g), and a random effects meta‐analysis was performed, including investigation of effect moderators. Quality of evidence was evaluated using GRADE. Results: Figure 1 summarizes risk of bias in various domains. We found moderate quality evidence of a small‐moderate effect of CT relative to control on the primary outcome, global cognition immediately following treatment (SMD=0.42, CI=0.23‐0.62, Figure 2), which was maintained at a medium‐term follow‐up. None of our pre‐specified factors moderated this effect. We also found high‐quality evidence of a moderate effect of CT on verbal semantic fluency (SMD 0.52, 95% CI 0.23‐0.81) at end of treatment, which was maintained in the medium term. No benefits of CT where found compared with an alternative treatment, and the quality of evidence in relation to most other outcomes was low, so we could not determine whether it was associated with meaningful benefits. Conclusions: This comprehensive updated review suggests, for the first time, that CT is associated with a small to moderate effect on global cognition and semantic fluency in people with mild‐moderate dementia. quality of evidence remains an issue, and confidence in the findings in relation to many meaningful outcomes remains low. References: Bahar‐Fuchs, A., et al. (2013). Cognitive training and cognitive rehabilitation for mild to moderate Alzheimer's disease and vascular dementia. Cochrane Database of Systematic Reviews, Issue 6. Bahar‐Fuchs A, et al. (2019). Cognitive training for people with mild to moderate dementia. Cochrane Database of Systematic Reviews. 2019(3).